1998
DOI: 10.1007/s004210050434
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory changes in the cold induced by physical training in humans

Abstract: It has previously been demonstrated that metabolic heat production (M) during cold exposure at rest was related to maximal oxygen uptake (VO2max). Consequently, an increase in VO2max could allow an increase M in the cold. The aim of the present study was therefore to test this hypothesis. Eight male volunteers undertook interval training (periods of 25% VO2max of 30-s duration and 110% VO2max of 60-s duration until exhaustion, five times a week over 8 weeks) to increase VO2max. Both before and after this physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Similar results have been previously reported by Henane et al (1977) and Savourey and Bittel (1998) after a similar interval training in a comfortable ambient temperature but for longer durations, 3 months (Henane et al 1977) and 2 months (Savourey and Bittel 1998) compared with 1 month in the present study. Body mass and body fat content did not change after the physical training and after the acclimation period.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Similar results have been previously reported by Henane et al (1977) and Savourey and Bittel (1998) after a similar interval training in a comfortable ambient temperature but for longer durations, 3 months (Henane et al 1977) and 2 months (Savourey and Bittel 1998) compared with 1 month in the present study. Body mass and body fat content did not change after the physical training and after the acclimation period.…”
Section: Discussionsupporting
confidence: 94%
“…The duration of the training protocol was identical between the two groups (10 min at the beginning up to 60 min at the end of the training period). This protocol was chosen because it is known to modify thermoregulatory responses, as previously reported (Henane et al 1977;Savourey and Bittel 1998).…”
Section: Physical Training Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cross-sectional comparisons of aerobically fit and less fit persons find no relationship between maximal aerobic power and temperature regulation in cold, and in studies purportedly demonstrating a relationship, differences in thermoregulation appear more likely attributable to anthropometric differences between the aerobically fit and less fit participants than to an effect of maximal aerobic power per se (20). Longitudinal studies have shown interval training to have no measurable effects on thermoregulatory responses to cold (207), and while endurance training was shown to improve the cutaneous vasoconstrictor response during cold water immersion, that effect had little impact on deep body temperature changes during cold exposure (277). There is some evidence (102) to suggest that the maximum shivering intensity is related to maximum oxygen consumption (VO 2max ).…”
Section: Individual Differences and Tolerancementioning
confidence: 97%
“…In addition, exercise training has been suggested to enhance the peripheral vasoconstriction response, which would conserve body heat but possibly increase peripheral cold injury risks. [87][88][89][90][91] Sex. The hypothermia injury rate for females is 2 times higher than for males.…”
Section: Nonenvironmental Risk Factorsmentioning
confidence: 99%